2014
DOI: 10.1002/ijc.28823
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs and cancer risk in women: Results from the Women's Health Initiative

Abstract: The use of non-steroidal anti-inflammatory drugs (NSAIDs) has been associated with reduced risks of cancers at several sites in some studies; however, we recently reported no association between their use and total cancer risk in women in a prospective study. Here we examine the association between NSAIDs and total and site-specific cancer incidence in the large, prospective Women’s Health Initiative (WHI). 129,013 women were recruited to participate in the WHI at 40 US clinical centers from 1993 to 1998 and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 46 publications
3
42
2
Order By: Relevance
“…In our study, however, we found no effect modification by obesity, and several other studies have also reported similar risk estimates for use of NSAIDs among obese and non-obese women [15,16,18,20,[32][33][34]37]. In fact, the differential effect of aspirin according to body mass index observed in the meta-analysis [6] was primarily driven by the results of two studies [35,36].…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…In our study, however, we found no effect modification by obesity, and several other studies have also reported similar risk estimates for use of NSAIDs among obese and non-obese women [15,16,18,20,[32][33][34]37]. In fact, the differential effect of aspirin according to body mass index observed in the meta-analysis [6] was primarily driven by the results of two studies [35,36].…”
Section: Discussioncontrasting
confidence: 57%
“…Consistent with [13,17,20,32,[34][35][36]. Among these are some large studies based on prospective data from the Women's Health Initiative [32], the Multiethnic Cohort [20], and the Nurses' Health Study [35]. Other studies, including a meta-analysis [6], have reported nonsignificant [15,16,33,37] or significant [6,18] endometrial cancer risk reductions associated with overall aspirin use.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We calculated prediction interval (PI) of summary estimate for the random effects model to depict the uncertainty around the estimate (17). If studies did not report a summary risk estimate for aspirin use, a summary risk estimate was calculated using risk estimates for each of the aspirin use categories (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Interstudy heterogeneity was estimated using a c 2 -based Q test (34), with a P value of <0.10 considered statistically significant (35).…”
Section: Discussionmentioning
confidence: 99%